Youth entrepreneurship dynamics in the Caribbean region: 2011-2013 (2017)
This paper presents the main results of the research work done in the Caribbean countries in the 2011-2013 period oriented to measure the dynamics of the youth entrepreneurs and their enterprises. The methodology used was GEM methodology, and the analysis is done using as framework the 'entrepreneurial pipeline concept' to make easier the understanding of the results, the identification of areas of improvement and the formulation of policies for entrepreneurship development. The entrepreneurial pipeline of the young population (18-34 years old), presents better indicators than the entrepreneurial pipeline of the adult population (35-64 years old), except in the 'established business' stage.